Fundamentals of Society Formation from the Viewpoint of Allameh Tabtabaei (RH) and its Implications in Social Training - Reza Ali Nowrouzi; Monireh Abedi (حکمت اسرا, 2012)
This article aims at investigating the quality of society formation from the viewpoint of Allameh Tabatabaei (RH) and eliciting the principles and methods of social training based on which. Three basic fundamentals have been discussed in this article including “the instinct of employment” as a basis for society formation, “inevitability of discrepancies within the society”, and “the importance of family status” as the first step for society formation. Based on these fundamentals, principles and methods of society training should be formulated in such a way that they can employ the instinct of employment to serve the individual and society, help resolve disputes, and be successful in maintaining and strengthening the relationships within the family. By investigating the Allameh Tabatabei's ideas in this area, we can find out its capability for developing such principles and methods. Therefore, by using an attributive - analytical approach and based on the fundamentals of society formation from the viewpoint of Allameh Tabtabaei (RH), the present article attempts to deduce the principles and methods of society training. The results show the effectiveness of social training in improving social relationships and solving problems of the society.